Evidence of a full West Antarctic Ice Sheet back to the early Oligocene: insight from double dating of detrital apatites in Ross Sea sediments. (28th April 2015) - Olivetti, Valerio; Balestrieri, Maria Laura; Rossetti, Federico; Thomson, Stuart N.; Talarico, Franco M.; Zattin, Massimiliano
Abstract The West Antarctic Ice Sheet is the most unstable component of the Antarctic cryosphere. Its fluctuations are well documented since the Pliocene, but its behaviour over the last 35 Ma is more controversial, particularly during periods of past high global pCO2 values similar to those predicted in future global climate scenarios. Here, we present new U–Pb dating of detrital apatite grains (previously dated by the fission‐track method) from Cape Roberts Project Oligocene to Pliocene marine sediments in the Ross Sea. Two past ice‐flow patterns were identified: one formed by outlet glaciers sourcing short‐travelled apatites and one, northerly directed, bringing far‐travelled apatite grains. The latter provides the first robust physical evidence for the presence and repeated expansion of an Oligocene West Antarctic Ice Sheet.